O FIM D'ARTISTA: DECONSTRUCTION AND RECONSTRUCTION OF THE SELF BY CREATIVE PROCESS (Palíndromo, 2018)
Analysis of how internalization of the other and exteriorization of itself can generate controversies between social identity and personal identity of each individual, taken from the theories of identity of French Philosopher Clement Rosset. Survey about women position as an artist and mother and, then, the lived reality in parallel between the creative act and motherhood.The study of deconstruction and reconstruction of the Self through the creative process. Theoretical practical methodology, that culminates with a production and analysis of the video O Fim d’artista, in 2016, taking as main practical references the artistic and autobiographic propositions from Louise Bourgeois, Mônica Mayers and Esther Ferrer, mainly. Thisarticleispartof a doctoralresearch. (2017. PPGAV-UFRGS).
Keywords: identity; the Self; the Other; women; motherhood